1996
DOI: 10.2535/ofaj1936.73.1_65
|View full text |Cite
|
Sign up to set email alerts
|

Light and Scanning Electron Microscopic Study on the Lingual Papillae in the Newborn Sea Otter Enhydra lutris

Abstract: The tongue of Enhydra lutris (sea otter), died from brain contusion at the first day of its age, was investigated by light and scanning electron microscopy in this study. Three types of papillae (filiform, fungiform and circumvallate papillae) were present on this tongue. In our evaluation, the filiform papillae were divided into four shapes which were conical, club-shaped, large horny and triangular papillae. The different types of filiform papillae were located in different area of this tongue. The fungiform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 6 publications
2
39
1
1
Order By: Relevance
“…In regards to the oral mucosa of Homosapiens, Caffesse et al, (1982) reported that mechanical stimulation of the sulcular epithelium plays a role in promoting its keratinization. Shimoda et al, (1996) examined the lingual mucosa of the aquatic mammal, the Sea Otter (Lutrinae: Enhydra lutris) and found a thin, but orthokeratinized cornified layer. The diet of sea otters consists of abalones, sea urchins, rock crabs and shellfish (Jefferson et al, 1993).…”
Section: Keratinizationmentioning
confidence: 99%
“…In regards to the oral mucosa of Homosapiens, Caffesse et al, (1982) reported that mechanical stimulation of the sulcular epithelium plays a role in promoting its keratinization. Shimoda et al, (1996) examined the lingual mucosa of the aquatic mammal, the Sea Otter (Lutrinae: Enhydra lutris) and found a thin, but orthokeratinized cornified layer. The diet of sea otters consists of abalones, sea urchins, rock crabs and shellfish (Jefferson et al, 1993).…”
Section: Keratinizationmentioning
confidence: 99%
“…In the order Carnivora, there have been some scanning electron microscopy (SEM) studies on the tongues of the cat (Boshell et al, 1982), dog (Iwasaki and Sakata, 1985), mongoose (Iwasaki et al, 1987), Japanese weasel (Furubayashi et al, 1989), sea otter (Shimoda et al, 1996), bush dog (Emura et al, 2000), panther and Asian black bear (Emura et al, 2001), lion (Emura et al, 2003), tiger (Emura et al, 2004) and jaguar (Emura et al, 2013). Such studies have revealed variations in the morphology and distribution of papillae on the dorsal lingual surface among animal species.…”
Section: Introductionmentioning
confidence: 99%
“…In the order Carnivora, there have been some SEM studies of the tongues of cat (Boshell et al, 1982), dog (Iwasaki and Sakata, 1985), mongoose (Iwasaki et al, 1987), Japanese weasel (Furubayashi et al, 1989), sea otter (Shimoda et al, 1996), bush dog (Emura et al, 2000), panther and asian black bear (Emura et al, 2001), lion (Emura et al, 2003), tiger (Emura et al, 2004) and silver fox (Jackowiak and Godynicki, 2004). Such studies reveal variations in morphology and distribution of papillae on the dorsal lingual surface among animal species.…”
mentioning
confidence: 99%